Peningkatan Motivasi Belajar Menggunakan Model Teams Games Tournament Mata Pelajaran IPAS Kelas V - Titisan Sukma Larasati; Tri Widiarto (JANACITTA, 2024)
This research aims to increase students' learning motivation in Class V Science and Science subjects at SDN Randuacir 02 Salatiga using the Teams Game Tournament model. The research method used was Classroom Action Research which was carried out over 2 cycles. The results of the research conducted showed an increase in students' learning motivation in the Science and Science subject, with an average percentage based on observations in the pre-cycle of 48.9%, an increase in cycle 1 of 76.3% and cycle 2 of 81.25%. The results of the student learning motivation questionnaire obtained a percentage increase from cycle 1 of 78.3% to cycle 2 of 82.3%. Thus, it can be concluded that the Teams Game Tournament model can increase students' learning motivation in science subjects at SDN Randuacir 02 Salatiga. Abstrak Penelitian ini bertujuan untuk meningkatkan motivasi belajar siswa pada mata Pelajaran IPAS Kelas V SDN Randuacir 02 Salatiga menggunakan model Teams Game Tournament. Metode Penelitian yang digunakan yaitu Penelitian Tindakan Kelas yang dilakukan selama 2 siklus. Hasil peneltian yang dilakukan terjadi peningkatan motivasi belajar siswa mata Pelajaran IPAS memiliki hasil motivasi belajar siswa dengan rata-rata persentase berdasarkan observasi pada Pra siklus sebesar 48,9% meningkat pada siklus 1 sebesar 76,3% dan siklus 2 sebesar 81,25%. Hasil angket motivasi belajar siswa diperoleh peningkatan persentase dari siklus 1 sebesar 78,3% pada siklus 2 sebesar 82,3%. Demikian dapat disimpulkan bahwa model Teams Game Tournament dapat meningkatkana motivasi belajar siswa mata Pelajaran IPAS di SDN Randuacir 02 Salatiga.